In silico and in vitro models reveal the molecular mechanisms of hypocontractility caused by TPM1 M8R - Creso, Jenette G.; Gokhan, Ilhan; Rynkiewicz, Michael J.; Lehman, William; Moore, Jeffrey R.; Campbell, Stuart G. (Frontiers in Physiology, 2024)
Dilated cardiomyopathy (DCM) is an inherited disorder often leading to severe heart failure. Linkage studies in affected families have revealed hundreds of different mutations that can cause DCM, with most occurring in genes associated with the cardiac sarcomere. We have developed an investigational pipeline for discovering mechanistic genotype-phenotype relationships in DCM and here apply it to the DCM-linked tropomyosin mutation TPM1 M8R. Atomistic simulations predict that M8R increases flexibility of the tropomyosin chain and enhances affinity for the blocked or inactive state of tropomyosin on actin. Applying these molecular effects to a Markov model of the cardiac thin filament reproduced the shifts in Ca2+sensitivity, maximum force, and a qualitative drop in cooperativity that were observed in an in vitro system containing TPM1 M8R. The model was then used to simulate the impact of M8R expression on twitch contractions of intact cardiac muscle, predicting that M8R would reduce peak force and duration of contraction in a dose-dependent manner. To evaluate this prediction, TPM1 M8R was expressed via adenovirus in human engineered heart tissues and isometric twitch force was observed. The mutant tissues manifested depressed contractility and twitch duration that agreed in detail with model predictions. Additional exploratory simulations suggest that M8R-mediated alterations in tropomyosin-actin interactions contribute more potently than tropomyosin chain stiffness to cardiac twitch dysfunction, and presumably to the ultimate manifestation of DCM. This study is an example of the growing potential for successful in silico prediction of mutation pathogenicity for inherited cardiac muscle disorders.